Stereoconvergent Arylations and Alkenylations of Unactivated Alkyl Electrophiles: Catalytic Enantioselective Synthesis of Secondary Sulfonamides and Sulfones - Choi, Junwon (American Chemical Society, 2014)
[Image: see text] The development of efficient methods for the generation of enantioenriched sulfonamides and sulfones is an important objective for fields such as organic synthesis and medicinal chemistry; however, there have been relatively few reports of direct catalytic asymmetric approaches to controlling the stereochemistry of the sulfur-bearing carbon of such targets. In this report, we describe nickel-catalyzed stereoconvergent Negishi arylations and alkenylations of racemic α-bromosulfonamides and -sulfones that furnish the desired cross-coupling product in very good ee and yield for an array of reaction partners. Mechanistic studies are consistent with the generation of a radical intermediate that has a sufficient lifetime to diffuse out of the solvent cage and to cyclize onto a pendant olefin.